“Infotainment”: Paradoks Liberalisme dan Representasi Moral Darwinisme Sosial - Puji Rianto (Program Studi Ilmu Komunikasi, 2008)
The infotainment program, which recently broadcasted a lot, summon controversial among the society. Nahdlatul Ulama even issued the fatwa haram. Purpose of this article is not to extend those arguments, but to explore the ideology beyond it, neo-liberalism and what is the impact Infotainment is a cultural industry product, broadcast in some television stations, which chase only to make a profit. In this situation, infotainment trapped into liberalism paradox, and in any level represent social darwinism moral. As we can see, the infotainment journalists pay a lot of attention to artists' personal life, which put some limitation to the artists themselves. In the other hand, to pursue higher rate, journalists frequently don’t care about other people in society.